(Studi Di Desa Patas I, Kecamatan Gunung Bintang Awai, Kabupaten Barito Selatan) - SISMA DIANTY (STISIP Widyapuri Mandiri Sukabumi, 2025)
This research discusses the effectiveness of collaboration between the Village Government and the Village Consultative Body (BPD) in an effort to improve infrastructure development in Patas I Village, Gunung Bintang Awai Sub-district, South Barito Regency. This research uses a descriptive qualitative method to provide a factual and accurate picture of the effectiveness of the collaboration. Data were obtained through observations, interviews, and documentation with purposive sampling techniques, involving the Village Head, Deputy BPD, and the local community as the main informants.The results show that the effectiveness of collaboration between the Village Government and BPD in village infrastructure development is strongly influenced by several factors, such as timeliness, cost calculation, measurement, and determination of development goals and objectives. The main supporting factors in this collaboration include good communication between the village government and BPD, active community involvement, and the availability of sufficient funds. However, this study also identified several inhibiting factors, such as budget limitations, lack of competent human resources, and administrative constraints.Based on the findings of this study, it is recommended that the village government and BPD improve synergy through more careful planning, budget transparency, and increased human resource capacity in village infrastructure development management. Thus, village development can run more effectively and provide maximum benefits to the community.